Tumor budding as an indicator of prognosis in locally advanced rectal cancer after neoadjuvant chemoradiotherapy: a systematic review and meta-analysis - Rafiee, Azita; Nasri, Parto; Moradi, Afshin; Karimian, Paridokht (Frontiers in Oncology, 2025)
IntroductionTumor budding (TB) is recognized as a complementary prognostic factor for colorectal cancer. However, data on its impact on the survival of patients undergoing neoadjuvant chemoradiotherapy (nCRT) remain limited. This study aims to investigate the role of TB in disease-free survival (DFS) and overall survival (OS) among patients with locally advanced rectal cancer receiving nCRT.MethodsIn this systematic review and meta-analysis, an exhaustive search of the PubMed, Scopus, Web of Science (WOS), Embase, and Cochrane databases was conducted, ultimately leading to the extraction of eight studies in the qualitative assessment and meta-analysis.ResultsAll the included studies were of high quality. The total sample size comprised 1,941 individuals. Although eight studies were included, nine datasets were extracted, as some studies reported multiple outcome measurements. TB positivity was statistically associated with decreased overall survival of 3.24 (95% confidence interval [CI]: 1.71–6.16) and disease-free survival of 2.54 (95% CI: 1.56–4.15) in patients with locally advanced rectal cancer undergoing nCRT.DiscussionBased on the findings of this study, TB negativity was statistically and directly associated with better OS and DFS in patients with locally advanced rectal cancer undergoing nCRT.